Survey on state scheduling-based topology control in unattended wireless sensor networks. (November 2016) - Renold, A. Pravin; Chandrakala, S.
Highlights: We survey the state scheduling-based topology control protocols suitable for unattended wireless sensor networks. We categorize the protocols based on the parameters used for state scheduling. Advantages, drawbacks, and results of existing methods are tabulated. We delineate future research issues in design of state scheduling-based topology control protocols. Abstract: Wireless sensor networks comprise nodes with limited power supply. The dense deployment of nodes on a terrain for monitoring the environment causes contention in wireless channels that leads to interference and high energy consumption. The topology of the network changes frequently because of failure of nodes, addition of new nodes, and channel fading. Topology control is an important technique for reducing energy consumption, interference, and maintaining connectivity in the network. This paper provides a survey on state scheduling-based topology control techniques for unattended wireless sensor networks. Topology control algorithms for both flat and hierarchical networks are discussed. The algorithms are further categorized according to the key parameters used for state scheduling. The advantages, disadvantages, and results of the algorithms are tabulated. In addition, we highlight future research directions in designing state scheduling-based topology control algorithms. Graphical abstract: